2003
DOI: 10.1046/j.1444-2906.2003.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-stimulating hormone beta, luteinizing hormone beta and glycoprotein hormone alpha subunit mRNA levels in artificially maturing Japanese eel Anguilla japonica and naturally maturing New Zealand longfinned eel Anguilla dieffenbachii

Abstract: cDNAs for three subunits of gonadotropin, namely follicle‐stimulating hormone (FSH) β, luteinizing hormone (LH) β and glycoprotein hormone (GP) α, of the New Zealand longfinned eel Anguilla dieffenbachii were cloned. Based on their nucleotide sequences, which were more than 98% identical to those of the Japanese eel Anguilla japonica, a real‐time reverse transcription–polymerase chain reaction method for the quantitative assay of gonadotropin subunit mRNAs of the two eel species was developed using the same pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 22 publications
3
22
2
Order By: Relevance
“…These results are in agreement with our previous studies, where an increase in pituitary content of LH hormone, as measured by RIA, was observed in experimentally matured eels [43]. In addition, our results are in agreement with those obtained in the Japanese eel, showing an increase in LHβ and GPα mRNA levels during the induction of ovarian development [44, 45]. These data indicate that the increase in pituitary LH synthesis during induced ovarian development in the eel is mediated by increases in LHβ and GPα mRNA levels.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results are in agreement with our previous studies, where an increase in pituitary content of LH hormone, as measured by RIA, was observed in experimentally matured eels [43]. In addition, our results are in agreement with those obtained in the Japanese eel, showing an increase in LHβ and GPα mRNA levels during the induction of ovarian development [44, 45]. These data indicate that the increase in pituitary LH synthesis during induced ovarian development in the eel is mediated by increases in LHβ and GPα mRNA levels.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, our results from in situ hybridization as well from dot-blot analysis indicate that, in untreated female silver eels, both FSHβ and LHβ were detectable and expressed at a low level, suggesting potential roles of the two gonadotropins during the early stages of vitellogenesis. Similarly, a low expression of FSHβ at the early vitellogenic stage was also observed in the New Zealand long-finned eel [45] contrasting a high expression of FSHβ found in the Japanese eel [45]. These studies suggest some common and some different features in the expression and potential roles of LH and FSH during gonadal development among different eel species.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Probably the reduction in FSHβ in the present study has been caused by an increase in testosterone induced by hCG injection. This decrease in the FSHβ expression has been also observed in European eel female after salmon pituitary extracts treatment [58], likewise in Japanese eel female [61][62][63] injected with salmon pituitary extracts or salmon gonadotropin fraction. In order to know if the gonadotropin profiles observed in artificially matured eels are similar to the natural pattern, Saito et al [63] compared the gonadotropin expression in naturally maturing New Zealand longfinned eel with artificially maturing Japanese eel.…”
Section: Discussionmentioning
confidence: 96%
“…This decrease in the FSHβ expression has been also observed in European eel female after salmon pituitary extracts treatment [58], likewise in Japanese eel female [61][62][63] injected with salmon pituitary extracts or salmon gonadotropin fraction. In order to know if the gonadotropin profiles observed in artificially matured eels are similar to the natural pattern, Saito et al [63] compared the gonadotropin expression in naturally maturing New Zealand longfinned eel with artificially maturing Japanese eel. With the first injections a quickly decrease in the FSHβ expression was observed in artificially maturing female eels, whereas in New Zealand longfinned eels in mid-vitellogenic stage a FSHβ increase was observed.…”
Section: Discussionmentioning
confidence: 96%